The Influence Of Training Quality And Learning Facilities On The Satisfaction Of Community Empowerment Training (Dpm) Participants In Basic Safety Training (Bst) Certification At Banten Merchant Marine Polytechnic, With Training Participants' Motivation A - Garit Fatrio; Aty Herawati (Jurnal Adijaya Multidisplin, 2025)
This study examines the impact of training quality and learning facilities on the satisfaction of participants in the Community Empowerment Training (DPM) Basic Safety Training (BST) certification at Banten Maritime Polytechnic, with participant motivation as a mediating variable. A quantitative approach using Structural Equation Modeling-Partial Least Square (SEM-PLS) was applied, with a sample of 115 participants determined using the Slovin formula at a 5% margin of error. The findings reveal that training quality does not significantly influence participant motivation (p-value = 0.225), whereas learning facilities have a significant effect (p-value = 0.000). Moreover, motivation positively and significantly affects training satisfaction (p-value = 0.000), indicating that highly motivated participants tend to be more satisfied. Training quality does not directly or indirectly influence satisfaction through motivation (p-value = 0.388 and 0.235), while learning facilities significantly affect satisfaction both directly and indirectly via motivation (p-value = 0.000). These results highlight the vital role of learning facilities in enhancing participant satisfaction. Therefore, improvements in training infrastructure should be prioritized to strengthen motivation and satisfaction levels. Recommendations for Banten Maritime Polytechnic include boosting participant motivation through incentives, enhancing instructor competencies, and integrating experience-based learning strategies. Future research should explore additional factors, such as instructor roles and psychological aspects, that may contribute to participant satisfaction.